Computation of stiffness derivative for an unsteady delta wing with curved leading edges - Monis, Renita Sharon; Shabana, Ayesha; Crasta, Asha; Khan, Sher Afghan (Institute of Institutional Industrial Research, 2017)
An attempt has been made to derive the expressions for stiffness derivative for a delta wing with curved leading edges for an unsteady high speed flow. It is evident from the figures that stiffness derivative decreases as Mach number increases. It is also seen that as amplitude of half sine wave increases the stiffness derivative also increases. This is an improvement of previous theory as the effect of leeward surface are included in the present work.